Evolution of Antonio Candido’s literary criticism on Vidas secas - Luna Filho, José Roberto de (2024)
In this work, we analyze three essays by Antonio Candido about the novel Vidas secas by Graciliano Ramos. In first two essays, the critic believed that the work belonged to the naturalism tradition, with the brutal connection between human beings and the land being central to the narrative, a theme also present in Os Sertões by Euclides da Cunha. However, later on, precisely on the fiftieth anniversary of the book, in a lesser-discussed essay, the critic revisits his positions, emphasizing this time how the representation of the inner richness of characters marginalized by culture is central to Graciliano's narrative. Following the evolution of this critical perspective allows us to grasp a rather complex and relevant understanding of both literature and the final novel of the writer, demonstrating the evolution of Candido's critical and theoretical thinking.